OBTAINING Artemisia cina POLYPLOIDY THROUGH PLANT GROWTH REGULATOR TREATMENT IN SHOOT CULTURE - Herawati, Maria Marina; Pudjihartati, Endang; Pramono, Suwijiyo; Sulistyaningsih, Endang; Purwantoro, Aziz (AGRIVITA, Journal of Agricultural Science, 2015)
Artemisia cina is a medicinal plant species which produces bioactive compound potential to anti-tumor, antifungal and antibacterial medicines. This study was aimed to obtain A. cina polyploid plants through a treatment of growth regulators in shoot culture. The shoot were treated in 1; 15; 2; and 3 mg L-1 of 2,4-dichloro phenoxy acetic acid (2,4-D) combined with 1; 1.5; 2; 3 mg L-1 of Benzyladenine (BA) for 28 days. Chromosome analysis showed that the highest polyploidy percentage, 23%, was reached in the treatment of 2 mg L-1 of 2,4-D combined with 1 of BA mg L-1. The polyploidy level varied, comprising 2n=3x, 2n=4x, 2n=5x, 2n=6x, with the highest polyploidy level percentage, 28.57%, and it was attained in the tetraploid (2n=4x). Polyploid plants had larger leaves area, larger stomatal size, and higher chlorophyll content than diploid plants. However stomatal density of polyploidy plants was lower than that of in diploid plants.